Persepsi Tentang Daya Tarik Iklan dan Pengaruhnya Pada Brand Exposure Produk Mie Instan - Ikbar, Harits; Firdausa, Faza Ruziqyani; Syamilah, Fidelia; Abillah, Muhammad Vicky; Cindy, Vira Deyana (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2023)
This study aims to examine consumer perceptions of the attractiveness of Instant Noodle advertisements and their effect on brand exposure. The method used was quantitative by distributing questionnaires to 136 respondents who had experience buying and consuming Instant Noodles. Data taken using Partial Least Square analysis. The results showed that consumer perception of advertising attractiveness has a significant positive influence on brand exposure. The managerial implication of this study is that companies should consider the attractiveness of advertising in their marketing strategy, and also pay attention to other factors that can affect brand exposure. Keyword: Advertising, Brand Exposure, Instant Noodles